Suppression pool testing at the SIET laboratory: experimental investigation of critical phenomena expected in the Fukushima Daiichi suppression chamber. Issue 5 (3rd May 2016) - Pellegrini, Marco; Araneo, Lucio; Ninokata, Hisashi; Ricotti, Marco; Naitoh, Masanori; Achilli, Andrea
Abstract : In the unlikely event of a nuclear power plant long duration station black-out, as in the Fukushima Daiichi (1F) severe accident (SA), it was recognized that the suppression chamber (S/C) functions of heat sink and fission product (FP) scrubbing will degrade, resulting in the S/C pressure increase, reduction of the scrubbing efficiency and subsequent necessity of venting operations. Consequently, a relatively large amount of FPs, in particular highly volatile elements (e.g. CH3 I), is likely to be dispersed into the environment. As a method to evaluate the degradation of the pool characteristics under discharge of steam and non-condensable gases through vent pipes and steam through different quencher geometries of make-up systems, an experimental campaign was recently started at the SIET research laboratory in Italy. Two different quencher geometries, representing vent pipes and the reactor core isolation cooling (RCIC) exhaust pipes in 1F2 and 1F3, were adopted. Several combinations of steam and air mass flow rates were tested to scale down the main conditions occurred during the 1F SA. Measurements of pool water temperature in different locations and visualization with high-speed camera represent the main outcome of the experimental activity. The preliminary results have demonstrated that a relatively small concentration of air in the steam flow is able to suppress the occurrence of chugging of the steam, with reduced mixing in the pool. Both RCIC quenchers adopted induced large chugging at the bottom of the pool which are effective to avoid temperature stratification, thanks to the large water recirculation and vertical mixing within the pool. At decreased subcooling, mixing in the pool ceases and the quenchers with holes disposed in the vertical direction, as in the RCIC exhaust pipe of the 1F unit 3, introduce intense stratification that drastically reduces the condensation efficiency of the S/C pool. Quencher of 1F2 RCIC does not present stratification possibly dependent on the distance of the pipe outlet to the pool floor. Given the reduced size of the pool compared to the plant scale, the observed phenomena should not be extrapolated for the whole S/C. The objective of the ongoing experimental activity is to construct a database based on the high-speed filming, measurements of major quantities such as water temperature, steam pressure and FPs concentration to foster the development of physical models for both lumped parameter SA codes and detailed computational fluid dynamics software, in an effort to enhance the understanding of the complex phenomena following the 1F accident.